Validación y seguimiento a la guía práctica de autocuidado para el paciente con diabetes mellitus tipo ii, UEB Hospital Alfredo Noboa Montenegro periodo octubre 2017 marzo 2018 - Barrágan Gómez, Liliana Alexandra (2018)
The present research work entitled: validation and follow-up to the practical self-care guide for patients with diabetes mellitus type II, UEB- Alfredo Noboa Montenegro Hospital for the execution of the same one planted the following problem: in what way the non-validation and follow-up of The practical guide of self-care affects the care, treatment and improvement of the quality of life in patients with type II diabetes mellitus to solve this problem. The following objective was established to validate and follow up on the practical self-care guide for the patients with diabetes Mellitus type II. The type of study was qualitative and quantitative, which aims to collect information based on natural behaviors through observation, inquiry that are subject to a critical study through reasoning, reflection, argumentation, reason, solidarity with users, studying them in a normal context of your daily life allowing an analysis and interpretation based on the development of charts and graphs that allow you to see the realities of patients' illnesses. For the validation of the self-care guide, a specialist in endocrinology and a graduate in nursing with years of experience and part of the health team of the diabetic club of the Alfredo Noboa Montenegro hospital performed the follow-up on the same. 30 members of the diabetic club a pre-test and a post-test to assess the level of knowledge of the practical self-care guide and show whether to improve their living conditions, where the techniques and instruments used for the collection of information were the observation , elaboration and application of a questionnaire. To do this, it is necessary to raise awareness among diabetes users through educational talks about a correct nutritional plan, healthy habits, preventive measures, exercise and guide the taking of medicines at the appropriate time. The scientific framework makes studies related to this topic below, you can find the methodological strategies with their results, conclusions, recommendations and finally find the annexes of the results.